Study of Prevalence of Sarcopenia in Chronic Liver Disease and its Impact on Outcomes - Evuri, Pavankumar; Selvi, Caroline; E, Manimekala; A, Aravind; Karunakaran, Premkumar; K, Muthukumaran; R, Murali; A, Chezhian; I, Shubha (International Journal of Innovative Research in Medical Science, 2022)
Background: Sarcopenia is the most common feature of chronic liver disease characterized by progressive loss of muscle mass and function and increases the mortality and morbidity rates among cirrhosis patients. The purpose of this study was to investigate the prevalence of sarcopenia in patients with chronic liver disease and its impact on outcome. Methods: This prospective observational study was conducted at institute of Medical Gastroenterology, Madras Medical college Chennai from September 2021 to May 2022 and included patients with chronic liver disease, graded by severity based on CTP and MELD Na scores. Sarcopenia was assessed according to EWGSOP 2 criteria. The association of lab parameters with Sarcopenia was studied. The outcomes of Sarcopenia were studied. Results: A total of 114 patients were enrolled in the study, 78.07% were male. The major etiology of Chronic liver disease was alcohol consumption (54.4%). The prevalence of sarcopenia was 54.3 %, with no significant differences between the male and female groups. Albumin, haemoglobin, Sodium, Handgrip, TPMT & Gait speed were significantly associated with sarcopenia. Mean CTP and MELD Na scores are high in sarcopenia group. Among the outcomes, we found that Ascites, Hepatic Encephalopathy & death are significantly associated with Sarcopenia. Conclusion: Sarcopenia is a common complication of liver cirrhosis and associates with adverse outcomes and poor survival rates.